Geography in the Construction of Knowledge in Administration (Terr@ Plural, 2022)
With the emergence of a globalized world, in which decisions depend on information from the most varied geographical scales, from local to global, it is essential that the management of companies, whether public or private, be based on a totality vision. Based on this assumption, the hypothesis of this study was to verify the presence of formalized Geography in the curricula of Administration courses (in higher education). The methodological procedures were based on a documental verification(by analyzing the curricula of the main Administration courses in the country),observing the data about the official formation of managers and how the curricula of these courses are constituted. A deficiency was verified in the educational process of administrators, with a lack of approaches to the fundamental notions of Geography during the teaching stages. This condition shows that the science of administration does not yet formally recognize the collaborative potential of Geography as a key discipline to stimulate the spatial thinking of managers and contribute to the comprehensive understanding of contemporary reality.
Keywords: Administration. Management. Administrative knowledge. Academic background